Tankyrase Inhibition Causes Reversible Intestinal Toxicity in Mice with a Therapeutic Index < 1. (February 2016) - Zhong, Yu; Katavolos, Paula; Nguyen, Trung; Lau, Ted; Boggs, Jason; Sambrone, Amy; Kan, David; Merchant, Mark; Harstad, Eric; Diaz, Dolores; Costa, Mike; Schutten, Melissa
Activated Wnt/β-catenin signaling is frequently associated with colorectal cancer. Wnt inhibitors, including tankyrase inhibitors, are being explored as potential anticancer agents. Wnt signaling is also critical for intestinal tissue homeostasis, and Wnt inhibitors have been shown to cause intestinal toxicity in mice by affecting intestinal stem cells. This study sought to characterize the intestinal toxicity of tankyrase inhibitors, including reversibility, and to assess their therapeutic index. Novel tankyrase inhibitor G-631 caused dose-dependent intestinal toxicity with a therapeutic index < 1 after 14 days of dosing in mice. At a tolerated subtherapeutic dose level, the intestinal toxicity was composed of enteritis characterized by villus blunting, epithelial degeneration, and inflammation, which fully reversed after 14 days of recovery. Doubled exposure showed weak antitumor activity in a xenograft colorectal cancer model but also caused more severe intestinal toxicity characterized by multifocal-regionally extensive necrotizing and ulcerative enteritis leading to morbidity or moribundity in some animals. This toxicity was only partially reversed after 14 days of recovery, with evidence of crypt and villus regeneration, mildly blunted villi, and/or scarring in association with chronic inflammation of the submucosa. Therefore, the clinical utility of tankyrase inhibitors is likely limited by the on-target intestinal toxicity and a therapeutic index < 1 in mice.